The Influence of Self-Efficacy on the Anxiety Levels of Students at the Faculty of Medicine Muhammadiyah Purwokerto University - Harum, Resmi Syahidah (Proceedings Series on Social Sciences & Humanities, 2025)
Anxiety is closely related to fear, where fear arises from something threatening. The aim of this research is to determine whether there is an influence of Self-Efficacy on the anxiety level of students at the Faculty of Medicine, Muhammadiyah University, Purwokerto. The hypothesis is that there is an influence of Self-Efficacy on the level of anxiety in Medical Students at Muhammadiyah University, Purwokerto. The higher the level of Self-Efficacy, the lower the level of anxiety students will have. This research is descriptive and analytical research. The results of this research provide answers that there is an influence of Self-Efficacy on the anxiety level of students at the Faculty of Medicine, Muhammadiyah University, Purwokerto.